Intercultural Philosophy - Mall, Ram Adhar (Rowman & Littlefield Publishers, 2000)
The meeting of different cultures, philosophies and religions today calls for an intensive and qualified discourse on the part of all concerned. Intercultural Philosophy seeks to develop such a discourse through a new orientation of thought that will allow for a discussion of all philosophical problems from an intercultural perspective. In this important new work, Ram Adhar Mall approaches the study of philosophy from a cross-cultural point of view allowing for fundamental similarities and illuminating differences between cultures. In doing so, he develops a new concept of intercultural philosophy and applies it to various philosophical disciplines.